Impact of accelerated aging of epoxy‐Ni nanocomposites on space charge variation adopting pulsed electro acoustic technique. (21st October 2020) - Sukesh Babu, Myneni; Amizhtan, Somasundaram Karthikeyan; Danikas, Michael G.; Sarathi, Ramanujam
Abstract: Epoxy‐Ni nanocomposites of different weight percentages are subjected to accelerated aging by water aging, thermal aging and UV irradiation to understand the influence of aging conditions on their space charge behavior. Homo‐charge accumulation is observed for unaged epoxy‐Ni nanocomposites. The magnitude of accumulated space charge is found to be lesser in 0.5 wt% epoxy‐Ni nanocomposite specimen compared to other unaged specimens. Water diffusion coefficient of epoxy‐Ni nanocomposites decreased with increasing weight percentage of filler addition. Space charge accumulation tends to increase with water aging. Increment in the space charge accumulation of 0.25 wt% epoxy‐Ni nanocomposite specimen is lesser compared to other water aged specimens. Exposure to thermal stress resulted in deterioration of the molecular structure of insulating material leading to an increase in trap‐controlled mobility, further leading to the reduction in space charge density with aging period. UV irradiation marginally assisted the charge transportation phenomenon, which resulted in the slight decrease of space charge density of epoxy‐Ni nanocomposites after UV irradiation. Hetero‐charge formation is found for all the three aging procedures. Overall, the specimen S1 reflected better space charge characteristics after being subjected to different aging conditions. Abstract : Mean magnitude of space charge density of epoxy‐Ni nanocomposites. Overall, it can be concluded that the specimen S1 (0.25 wt%) has exhibited better performance.